Plasma Cell Neoplasms in US Solid Organ Transplant Recipients. Issue 6 (1st May 2013) - Engels, E. A.; Clarke, C. A.; Pfeiffer, R. M.; Lynch, C. F.; Weisenburger, D. D.; Gibson, T. M.; Landgren, O.; Morton, L. M.
Abstract: Transplant recipients have elevated risk for plasma cell neoplasms (PCNs, comprising multiple myeloma and plasmacytoma), but little is known about risk factors in the transplant setting. Through linkage of the US solid organ transplant registry with 15 state/regional cancer registries, we identified 140 PCNs in 202 600 recipients (1987–2009). PCN risk was 1.8‐fold increased relative to the general population (standardized incidence ratio [SIR] 1.80, 95%CI 1.51–2.12). Among cases, 102 were multiple myeloma (SIR 1.41) and 38 were plasmacytoma (SIR 7.06). PCN incidence increased with age, but due to the rarity of PCNs in younger people in the general population, SIRs were highest in younger transplant recipients (p = 0.03). PCN risk was especially high in recipients who were Epstein‐Barr virus (EBV) seronegative at transplantation (SIR 3.93). EBV status was known for 18 tumors, of which 7 (39%) were EBV positive. Following liver transplantation, PCN risk was higher in recipients with cholestatic liver disease (SIR 2.78); five of these cases had primary biliary cirrhosis (PBC). A role for primary EBV infection after transplantation is supported by the increased PCN risk in young EBV seronegative recipients and the presence of EBV in tumors. PBC may be another risk factor, perhaps by causing chronic immune activation. Abstract : In this large US population‐based study, the authors demonstrate that transplant recipients have an elevated risk for plasma cell neoplasms and document several risk factors for this type of malignancy, including Epstein Barr virus infection, recipient age, and the presence of primary biliary cirrhosis.